Twitter in the Context of the Arab Spring - Abdul-Mageed, Muhammad; Brown, Christopher; Abu-Elhij’a, Dua’a (AoIR Selected Papers of Internet Research, 2013)
Except for some initial analyses (Authors, 2011; 2012; 2013), Arabic Twitter has not been the target of much research. Although these initial analyses have accumulated insights as to some Twitter user practices and the micro-blogging service’s content, these studies remain limited in terms of scale (i.e., they did not depend on huge datasets as is attempted in the current work), nor did they examine Twitter use and practices in the context of the Arab Spring. In the current work, our goal is to bridge these gaps. In other words, we investigate (1) the employment of various Arabic varieties, (2) sentiment expression, and (3) topic distribution in two Twitter sub-corpora, one pre-dating the Arab Spring and another occurring in its context. Our analyses show the impact of the political events on the social network at the three fronts.